Malaysia’s complex multi-level climate governance between institutionalization and non-state actor interventions - Zen, Irina Safitri; Mohamad, Zeeda F. (ROUTLEDGE, 2021)
As a fast-industrialising emerging economy, Malaysia is highly dependent on fossil fuels – making it an increasingly significant contributor to global warming. Since 2009, the country has made a clear commitment to address the issue by introducing a dedicated climate change policy and multi-level governance strategy with a voluntary reduction target of up to 40 percent in terms of emissions intensity of GDP by 2020 compared to 2005 levels. Despite a promising institutional framework and governance strategy, Malaysia’s low carbon transition has been stymied by various factors. In this chapter, we reveal how Malaysia’s socio-economic and socio-political context has resulted in an uncertain environment to consistently implement the climate change policy and governance strategy as originally planned. However, the proactive response from the sub-national government, non-partisan efforts and cooperation by non-state actors such as the private sector and academia have played an important bridging and initiating role in contributing significantly during this period of political uncertainty. Through a case study of Malaysia’s experience in the implementation of green technology in the State Melaka and low-carbon cities in the State of Johor, we illustrate the dynamic role of state and non-state actors in filling the void and weaknesses in climate change governance.